The effects of vacuum annealing temperatures on the microstructure, mechanical properties and electrical resistivity of Mg–3Al–1Zn alloy ribbons. (May 2015) - Chen, Fenghua; Huang, Qingxue; Jiang, Zhengyi; Zhao, Jingwei; Sun, Binyu; Li, Yugui
Abstract: This paper investigates the influence of vacuum annealing temperature on the microstructure, mechanical properties and electrical resistivity of Mg–3Al–1Zn rapid solidification (RS) magnesium ribbons. The results indicate that when the annealing temperature is increased, the grain size of the ribbons is dramatically reduced from 10 to 1 μm. The highest break stress and micro-hardness is obtained at 673 K. These effects are ascribed to the dispersion strengthening caused by the high amount of fine nanoparticles distributed in the material. Electrical resistivity-temperature ( ρ–T ) curves have been used to provide useful information about the effects of the annealing temperature on the grain size, grain orientation and crystal structure of the ribbons. In this way, a new lightweight electric wire or connection cable line could be produced which would have good electromagnetic interference (EMI). Highlights: The vacuum annealed temperature great affect the grain size from 10 um to 1 um. The highest break stress and micro-hardness of the sample with annealed at 673 K. A high amount of fine nanoparticles (20 nm) appear in the material. The electrical resistivity decreases, get a good resistivity of 61.9 nOmhs m.